Synthesis and characterization of modified SBA-15 for CO2 reforming of CH4 - Setiabudi, Herma Dina; Nurul Aini, Mohamed Razali; Mohd Zahari, Mior Ahmad Khushairi; Abdullah, Syamsul B. (2017)
CO2 reforming of CH4 has been studied extensively using variety of metal supported catalyst, including Ni/SBA-15. However, during lengthy stability testing, Ni/SBA-15 is gradually deactivated because of carbon deposition. Owing to the fact that the preparation of well dispersed Ni/SBA-15 is desired to inhibit carbon formation, thus the effects of TEOS/P123 mass ratio (1.5, 2.21 and 3.0), amount of Ni loading (3, 5 and 10 wt%) and Ni-loading method (impregnation (IM), ion exchange (IE) and physical mixing (PM)) on the properties and catalytic activity of Ni/SBA-15 were studied. The catalysts were characterized using XRD, BET, SEM, TEM, H2-TPR and TGA, while the catalytic activities were carried out using microcatalytic reactor. For the effect of TEOS/P123 ratio, the result clearly indicated that TEOS/P123 mass ratio of 2.21 was the optimal synthesis ratio of Ni/SBA-15 which produces the well-ordered hexagonal mesoporous structure with the highest Ni-support interaction, Ni–O–Si. The catalytically favorable textural properties of Ni/SBA-15(R2.21) enhanced the dispersion of metal particles, improved the catalyst activity, increased the catalyst stability and reduced the carbon deposition. For the effect of Ni loading, the result showed that the maximum formation of Ni–O–Si were achieved at 5 wt%, while further increased in Ni loading stimulate the agglomeration of Ni particles. The presence of Ni–O–Si in 5Ni/SBA-15 enhanced the stabilization of the active Ni species on SBA-15 support, minimized the growth of encapsulating graphite carbon and thus enhanced the activity and stability of catalyst. For the effect of Ni-loading method, the result showed that the Ni/SBA-15(IE) has higher formation of Ni–O–Si, which altered the properties of catalyst towards an excellent catalytic performance. This study successfully prepared well dispersed Ni/SBA-15 using IE method with TEOS/P123 of 2.21 and 5 wt% Ni loading.